The Global Peace Mandate of the United Nations Security Council, Conflict Management and the Israeli-Palestinian Question - Summersett, Glorious Preye; Alade, Adebola A. (Journal of Contemporary International Relations and Diplomacy, 2022)
The United Nations global conflict management strategy is based on certain fundamental assumptions that require serious re-examination in the twenty-first century. This study is focused on the United Nations Security Council, its global peace maintenance responsibility mandated by the United Nations Charter and the protracted Israeli-Palestinian conflict. The doctrinal approach was employed for this study. This is with aim to assess the long-standing violence between Israel and Palestine and a possible way of effective management and possible resolution, which is the sole responsibility of the United Nations Security Council. The study shed more light on the role of the Security Council, its efforts and its challenges that are hampering warring nations from settling their disputes. The study concluded that, although the United Nations Security Council has played vital roles in instituting global peace, which is the fundamental principle of macroeconomic stability, the reforms of the Council is at the top of the most pressing global political issues facing the international community. Therefore, among the recommendations of this study is that, the reformation of the Council to mirror the present globalized world political order is of utmost significance in order to provide room for effective regional or continental representation, just as a representative government is well suited for a federating country. This would enable effective representation via regional or continental powers creating a platform for feasibly effective conflict management and possible resolution of interstate conflicts.